Isolasi Bakteri Rhizosfer Tanaman Nilam (Pogostemon cablin Benth.) yang Berpotensi sebagai Penghasil Senyawa Antibakteri terhadap Bakteri Penyebab Infeksi Saluran Pencernaan - Maulidiyah, Zakiya; Dali, Seniwati; Rusli, Rusli; Naid, Tadjuddin (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Research on isolation of rhizosphere bacteria in patchouli (Pogostemon cablin Benth.) Plants. This study aims to obtain patchouli plant rhizosphere bacteria which have the potential to produce antibacterial compounds against bacteria that cause digestive tract infections. The first stage, isolation of bacteria originating from the patchouli plant rhizosphere. Antibacterial screening test using a match method, obtained IBRN-3 and IBRN-5 isolates inhibited the growth of all test bacteria. IBRN-3 and IBRN-5 isolates were fermented. The fermentation results are extracted with ethyl acetate solvent to produce dry fermentate ethyl acetate extract. Thin Layer Chromatography was identified on the ethyl acetate extract of IBRN-3 and IBRN-5 using chloroform: methanol (8: 1) eluent and followed by TLC-Bioautography test. The results of spotting on IBRN-3 with Rf value 0.93 inhibited the bacteria E. coli, S. aureus, Rf value 0.82 inhibited B. subtillis, S. dysenteriae, Rf value 0.64 inhibited S. aureus and S. thypii, Rf value 0.89 , 0.36, 0.24 inhibited S. dysenteriae, Rf values ​​0.84 and 0.74 inhibited S. aureus. Whereas for IBRN-5, spots were obtained with an Rf value of 0.91 inhibiting B. subtillis, E. coli S. thypii, an Rf value of 0.95 inhibiting S. aureus S. dysenteriae, an Rf value of 0.84 inhibiting B. subtillis, S. thypii, Rf value of 0.83 inhibits S. dysenteriae, and Rf value of 0.74 inhibits S. thypii.